Restoration of declining soil carbon stocks and lost surface elevations in degraded mangroves on the northern coast of Java, Indonesia - Trialaksita Sari Priska Ardhani; Trialaksita Sari Priska Ardhani; Cecep Kusmana; Dietriech Geoffrey Bengen; Joeni Setijo Rahajoe; Phidju Marrin Sagala; Bayu Budi Hanggara; Yohanes Risky Shellen Ginting; Milkah Royna; Daniel Murdiyarso; Daniel Murdiyarso (Frontiers in Ecology and Evolution)
Restoring degraded coastal zones could help to stem the loss of carbon (estimated by soil carbon differences) and soil surface elevations (measured through rod surface elevation table and marker horizon) due to mangrove conversion and sea-level rise. In mangroves, total ecosystem carbon stocks are primarily stored in soil, however the presence of vegetation remains crucial. When we assessed soil carbon across contrasting land uses in Wedung and Sayung Districts in Demak Regency, Central Java, we found that converting mangrove to aquaculture increased soil carbon by 17.68 Mg C ha-1 in Wedung but decreased it as much as 62.58 Mg C ha-1 in Sayung. Meanwhile, abandonment of ponds resulted in a loss of 34.24 Mg C ha-1 in Wedung but a gain of 8.81 Mg C ha-1 in Sayung. The estimated local sea-level rise of 0.45 cm yr-1 led to relative sea-level rises of 5.56, 6.82, and 1.36 cm yr-1 in mangroves, working and abandoned ponds respectively in Wedung, and 8.00, 10.39, and 10.46 cm yr-1 respectively in the same environments in Sayung. This indicates that Sayung is more severely inundated. After considering land subsidence levels, only mangroves in Wedung experienced an elevation surplus of 2.02 cm yr-1. The remaining land uses suffered elevation deficits, hence being inundated by 1.86 and 15.00 cm yr-1 in abandoned ponds in Wedung and Sayung respectively. Despite variation in this study’s findings, some scenarios could be considered useful to support relevant coastal areas to enhance soil carbon stocks or surface elevation.